Pride Aside: James Dundas as a Stoic Christian. Issue 2 (June 2019) - Gellera, Giovanni
Abstract : In the manuscript Idea philosophiae moralis (1679), James Dundas (c.1620−1679), first Lord Arniston, a Presbyterian, a judge and a philosopher, makes extensive use of Stoic themes and authors. About one third of the manuscript is a close reading of Seneca. Dundas judges Stoicism from the perspective of Calvinism: the decisive complaint is that the Stoics are 'prideful' when they consider happiness to be within the grasp of fallen human reason. However, pride aside, Dundas is willing to recover some Stoic insights for his Calvinist faith. In what ways? The promise of the practical rewards of Stoicism (control of the passions, tranquillity of the mind, strength of character) drives Dundas's interest in arguing that Stoicism can play a crucial psychological and moral contribution to a Christian's life. The investigation of Stoicism in the Idea philosophiae moralis sheds new light on the backdrop of the Scottish Enlightenment's relationship with Stoicism, commonly characterised as 'Christian Stoicism', as well as on the variety of the early modern Christian-Stoic syntheses, such as the Religio Stoici (1663) by George Mackenzie of Rosehaugh, a friend of Dundas's.